Boże miłosierdzie jako źródło chrześcijańskiego nonkonformizmu (Rz 12,1-2[8]) - Gieniusz, Andrzej 1958- (2003)
The article discusses the content of Rm 12,1-8 and its function in the entire argument of the Letter to Romans. lt argues that the first two verses o f the passage (Rom 12: 1-2) offer under the headline of God's mercy a summary of the previous theological content of the Letter (chs. 1-11) and at the same time serve as a foundation (propositio) for all the moral teaching of the subsequent chapters, while vv. 3-8 present the first practical example of the response to God's mercy in the internal life of a Christian community. The paradoxical and, according to the human standards, incomprehensible logic of God's merciful ways in dealing with humanity turns out to be both the source and the paradigm of any Christian moral life. His mercy, in fact, enables and calls believers to serve God "logically", i.e. to present themselves as a living sacrifice and ,,not to be confonned to this world".
Keywords: 1-8; Rz 12; List do Rzymian; miłosierdzie